Penerapan Pelatihan dan Pengembangan Karir pada Karyawan PT. KASAI TECK SEE Indonesia Kabupaten Karawang - Islami, Rizqa Aulia; Fadli, Uus Mohammad Darul (Journal of Economics and Management, 2023)
This study used a quantitative descriptive approach. The locus of this research at PT. Kasai Teck See Indonesia Karawang, the information is 3 managers and 27 staff selected by purposive sampling data collected through the distribution of questionnaires Data collection techniques use survey methods with questionnaire distribution, namely providing a list of questions or statements to respondents to obtain information needed in research. The type of data measurement scale used is the Rikert scale. The reason researchers use the rikert scale is because it is easier for respondents to understand, and does not take much time to answer. Title Application of Training and Career Development in PT. Kasai Teck See Indonesia. The respondents are managers and production staff. The population is 200 people, and the sample is 33 people calculated by the Slovin formula at an error rate of 5%. Furthermore, the data is collected through Likert scale and disseminated using google form. Against the questionnaire conducted vadiltas and reliabilita tests on 30 samples, it was concluded that the results of this study provide new nuances for implementation in the application of training and career development to employees in the company.